Pengaruh Sistem Pelacakan Online, Ketepatan Waktu Dan Keamanan Terhadap Kepuasan Pelanggan J&T Express Lowokwaru Kota Malang (Studi Pada Mahasiswa FEB Universitas Islam Malang) - Lutha, Isnaini Aulia; Nurhajati, Nurhajati; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to test and explain the influence of online tracking systems, timeliness and security on customer satisfaction of J&T Express Lowokwaru Malang City, case study among students at the Faculty of Economics and Business, Islamic University of Malang. This research uses a quantitative approach which uses the Maholtra formula in determining the sample because the population is still not known for certain. Looking at the calculation results of the Maholtra formula, the sample size is 90. To solve the problem in this research, SPSS is used to analyze the various tests carried out. such as validity tests, reliability tests, normality tests, classical assumption tests, hypothesis tests, multiple linear regression tests and adjusted R2 coefficient of determination tests. The results of this research are that the online tracking system, timeliness and security have a simultaneous effect on customer satisfaction and partially the online tracking system, timeliness and security have a significant effect on customer satisfaction. Keywords: Online Tracking System, Timeliness, Security, Customer Satisfaction